Shipwreck Hauntography : Underwater Ruins and the Uncanny - Rich, Sara A. (Maritime Humanities, 1400-1800: Cultures of the Sea, 2021)
Drawing on a broad theoretical range from speculative realism to feminist psychoanalysis and anti-colonialism, this book represents a radical departure from traditional scholarship on maritime archaeology. Shipwreck Hauntography asserts that nautical archaeology bears the legacy of Early Modern theological imperialism, most evident through the savior-scholar model that resurrects--physically or virtually--ships from wrecks. Instead of construing shipwrecks as dead, awaiting resurrection from the seafloor, they are presented as vibrant if not recalcitrant objects, having shaken off anthropogenesis through varying stages of ruination. Sara Rich illustrates this anarchic condition with 'hauntographs' of five Age of 'Discovery' shipwrecks, each of which elucidates the wonder of failure and finitude, alongside an intimate brush with the eerie, horrific, and uncanny.